Model Kepemimpinan Situasional Kepala Sekolah Dalam Penguatan Budaya Disiplin Siswa Berbasis Nilai Religius di SMK Muhammadiyah 2 Andong - Aditiya Fachrie Zanardi Abdurrahman; Mutohharun Jinan (Jayapangus Press, 2026)
Student discipline and religiosity in vocational schools often remain fragmented, as rule enforcement is not always integrated with internal value formation. This study aims to analyze the implementation of situational leadership by the school principal in strengthening students’ discipline and religious character at SMK Muhammadiyah 2 Andong. This research employs a qualitative descriptive approach with a phenomenological perspective. Data were collected through in-depth interviews, participatory observation, and documentation involving the principal, teachers, and students selected purposively. The findings reveal that the principal applies situational leadership adaptively by adjusting leadership styles, namely directing, coaching, supporting, and delegating, based on students’ readiness levels. The strengthening of discipline and religiosity is implemented through four main strategies: role modeling, habituation, educational approaches, and continuous evaluation. These strategies effectively transform external compliance into students’ internal awareness, leading to sustainable discipline and religious character. The study concludes that situational leadership based on religious values is effective in integrating discipline and religiosity into a unified character-building framework. This research provides a conceptual model of value-based situational leadership, derived from empirical analysis, that emphasizes the integration of adaptive leadership and internalization of religious values in shaping student character.